Moral spiritual value preferences of public secondary teachers in Quezon City - Cruz, Grace 1947- (s.n.], 1971)
The moral-spritual value preferences of public secondary teachers in Quezon City were determined. The sample consists of 369 teachers from the sixteen public secondary schools in Quezon City. The basic sources of data are the personal data questionnaire and the NCCSDFCY value scale.